PENGARUH RETRIBUSI PELAYANAN KESEHATAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SUMBAWA - Sri Rahayu; Verinda Tri Sugistiawati; Ika Fitriyani (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of health service fees on Locally-Generated Revenue (PAD) in Sumbawa Regency. This type of research is associative research. The associative type used in this study aims to determine the effect of health service fees (X) on Locally-Generated Revenue (PAD) of Sumbawa Regency (Y). The type of data used is quantitative data in the form of data on the realization of receipt of health service fees from 25 service counters of the Community Health Center in each sub-district in Sumbawa Regency, the realization of receipt of fees for health services at the Hospital and the realization of Locally-Generated Revenue (PAD) for Sumbawa Regency which obtained documents and archives from the Central Agency. Statistics (BPS) of Sumbawa Regency which have been published. All collected data were processed with the help of the SPSS application to be analyzed using techniques which included simple linear regression analysis, partial hypothesis testing (t test), and determination coefficient test (R2). Based on the results of the research has been concluded that health service fees have a positive and significant effect on Locally-Generated Revenue (PAD) in Sumbawa Regency. The degree of influence of health service fees on Locally-Generated Revenue (PAD) of Sumbawa Regency is 49.4%, while the remaining 50.6% is influenced by other variables beyond the scope of this study, such as blood tax, regional fees other than health service fees, and others.